Financial inclusion for economic sustainability: a systems thinking approach - Mungar-Jackpersad, Aviksha; Telukdarie, Arnesh; Tshukudu, Christian (Springer International Publishing, 2025)
Abstract Financial inclusion remains a global concern due to the intricate interdependencies among various influencing factors. This research adopts a systems thinking framework to analyse these interconnections and address them. A mixed-methods approach was employed, integrating both qualitative and quantitative methodologies. The qualitative analysis included a systematic literature review, database search, and the PRISMA framework to identify key variables influencing financial inclusion. The quantitative component utilised a word-to-vector methodology to measure semantic relationships among these variables. The findings reveal that while individual factors significantly impact financial inclusion within isolated themes, their influence diminishes when analysed within the broader systemic context. This aligns with the principles of systems thinking, emphasising the complexity of large-scale systems and the interconnected nature of variables. By visualising and quantifying these relationships, the study highlights the limitations of addressing financial inclusion through isolated interventions. The findings underscore the need for integrated, multi-faceted strategies considering systemic interactions. These insights provide a foundation for policymakers and stakeholders to develop more targeted, effective interventions that promote equitable economic development. By understanding how key variables interact within the more extensive system, decision-makers can design policies that address financial inclusion more holistically, ensuring sustainable and impactful solutions across diverse regions. This research contributes to the growing discourse on financial inclusion by offering a structured, data-driven approach to understanding its complexities and guiding strategic policymaking efforts. Keywords Financial inclusion · Financial technology · Economic development · Systems thinking